Utilization of indigenous potato (Solanum tuberosum) varieties as a source of micronutrient - DALAMU, DALAMU; SHARMA, JAGDEV; CHOUDHARY, BABITA; LUTHRA, SK (The Indian Journal of Agricultural Sciences, 2022)
Potato (Solanum tuberosum L.) is the most important non-grain food crop globally. Efforts are being made to breed biofortified potato varieties to mitigate malnutrition. Knowledge about micronutrient content is beneficial from nutritional and health view point. Sixty-three indigenous or desi potato varieties were evaluated for micronutrient content in whole tuber and tuber flesh. Mineral content of whole tuber was higher than tuber flesh alone depicting peel contains micronutrients. The zinc, iron, copper and manganese content in whole tuber on dry weight basis varied from 14.66-30.27, 26.82-48.15, 5.29-17.87 and 7.51-28.79 mg/kg or ppm, respectively, while in tuber flesh, the range was 13.67-26.71, 18.11-40.27, 4.48-16.91 and 5.81-21.46 mg/kg, respectively. Moderate correlation observed between iron and zinc content (r=0.483) and manganese and copper content (r=0.354) in tuber flesh implies possibility of simultaneous selection. Significant positive correlation of tuber flesh elemental content to that of whole tuber signifies the higher contribution of tuber flesh to overall nutrient content of whole tuber compared to potato peel deterring the misconception that majority of potato nutrients are found in the peel. NJ 130, Lal Jyoti, Desi No.1, V2 2912, Aruconia, DRR Red, Sathoo and JG-1 were high in individual and combined minerals. This study signifies that potato indigenous or desi varieties are potential source of micronutrients particularly zinc. Production of disease free seeds of the varieties particularly by farmers needs to be emphasised. Identified accessions may serve as parental lines in breeding nutrient rich potatoes.